Estudo da alteração da cor e degradação da clorofila durante armazenagem de erva-mate tipo chimarrão - Malheiros, Gisela Cabral (2007)
Ilex paraguariensis A. St.-Hill., popularly known as erva-mate (Portuguese) or yerba-mate (Spanish), is a native species of the subtropical region of South America, and it is raw material for the product also named erva-mate or yerba mate, consumed mainly under an infusion form called chimarrão (Portuguese) or mate (Spanish). Among the sensorial attributes of erva-mate chimarrão type, color is the first criteria used by consumers to measure its acceptability. The green color of erva-mate is due the presence of chlorophyll. Expressive chlorophyll losses occur during processing and storage of erva-mate, but the mechanisms and products formed are not well known yet. There are many possible pathways for the chlorophyll degradation, because it is sensitive to pH, enzymes, oxygen, temperature and light, and the rate of reactions are determined by the water activity of the food. The aim of this work was to evaluate the color and chlorophyll changes and to verify their causes during storage of erva-mate chimarrão type under ambient conditions, in the most common packaging materials. Samples of erva-mate chimarrão type, conditioned in laminated flexible film or paper, were stored in a chamber (25° C; relative humidity 75%), and analyzed at seven moments (0, 2, 4, 6, 8, 10 and 12 weeks of storage). The physicalchemistry analyses were: moisture, water activity, pH, TBARS and residual activity of peroxidase; quantification of chlorophyllian pigments (chlorophyll and pheophytin); instrumental color analysis by tristimulus colorimetry (obtaining L*, a*, b*, DE*, h° and C*). The results showed that the storage time and the kind of packaging significantly influenced all the items analyzed, except peroxidase, which did not present any residual activity. The analysis of chlorophyllian pigments presented controversial results, but their degradation was verified. Inside the paper package, the main erva-mate color changes were h° reduction (from the initial green to a more yellow green), L* reduction (darkening) and C* reduction (loss of color brightness, from bright-green to a more opaque green). Inside the laminated package, the main color changes were h° reduction (from the initial green to a more yellow green, but less accentuated than the paper package), L* increase (whitening) and C* reduction (loss of color brightness, from bright-green to a more opaque green, more expressive than the paper package). It was concluded that the color change was probably influenced by oxidation as well as by pheophytinization of chlorophyllian pigments in ervamate chimarrão type, and the predominant chlorophyll degradation reactions were pheophytinization inside the paper package and pheophytinization and oxidation inside the laminated package.